A CONCEPTUAL AND CLINICAL STUDY OF APARA (PLACENTA) - Dnyaneshwar Sudhakar, Meshram; Omprakash, Harode Meena; Kiran Bhikaji, Pawar; Vilas Pundlikrao, Borse; Ramkrushna Suryabhan, Nehare (International Journal of Ayurveda and Pharma Research, 2015)
Comparative study of Sharir (anatomical and physiological) terms from Samhita text with modern scientific terms has became needful today. Apara described in Samhita text is important structure for Garbha (fetus). Samhita description says it is formed by obstructed Artava (menstrual blood). It lies in relation to the maternal heart and provides nutrition to the developing Garbha through Garbhanabhinadi (umbilical cord). It sheds off after Prasuti (labour). This indicates Apara to be the Placenta from modern anatomical term. Its formation described from obstructed Artava may be because of resemblance of its maternal surface with blood clots and absence of Artava in Garbhavastha (pregnancy). Samhita description lacks its actual location and anatomical features. It is also called as Jarayu indicating different meanings in Kasyapa Samhita, Sushruta Samhita and Caraka Samhita. These facts indicate the need for its literary research. For anatomical study 30 pregnant females were selected randomly and their gestational ultrasonography was taken in third trimester to see the location of Apara (placenta) and abnormality. It is found that Apara is normally adhered to upper uterine segment. Apara received after labor from these selected 30 pregnant females were observed for anatomical features. The parameters noted for weight, diameter, thickness at center, number of cotyledons, attachment of umbilical cord at center or periphery, and abnormality of Apara. Observations given in charts and graphs. Lacuna in Samhita text regarding anatomical features of Apara needs the study of term Placenta.